Whistleblowing and Diffusion of Responsibility: An Experimental Investigation - Veronika Grimm; Lawrence Choo; Gergely Horvath; Kohei Nitta (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Societies today are increasingly reliant on whistleblowing to uncover unfair practices. For policy design it is therefore essential to better understand the impact of socio-psychological factors on whistleblowing propensity. We use an experimental setup to explore the role of “Diffusion of Responsibility” (DOR), which posits that individuals are less likely to whistleblow when others could similarly do so. We find that individuals do not shift responsibility to others if they expect an own monetary benefit from the consequences of whistleblowing, even if they could gain even more by freeriding on others who take action. In contrast, DOR affects whistleblowing propensities severely if whistleblowing is motivated solely by altruistic concerns. Our results highlight the fragility of purely altruistic behaviour and suggest that whistleblowing policies should ensure that potential whistleblowers perceive a gain to their in-group, but need not address the free riding problem among the insiders.
Keywords: C91; C92; D02; 330